2000
DOI: 10.1001/archsurg.135.10.1154
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β3 Promotes Fascial Wound Healing in a New Animal Model

Abstract: Transforming growth factor ␤ 3 (TGF-␤ 3) promotes fascial wound healing in a new animal model, as measured by wound breaking strength, collagen deposition, and cellular proliferation. Design/Intervention: Bilateral, longitudinal incisions were made in the anterior rectus sheaths of 24 male New Zealand white rabbits. One incision was treated with 1 µg of TGF-␤ 3 ; the contralateral incision served as a control. The wounds were harvested at 1, 2, 3, 4, 6, and 8 weeks after creation ("wounding"). Main Outcome Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…1 It has been suggested that TGFb3 supports scarless wound healing through modulation of the inflammatory response and the recruitment of fibroblasts to the wound site while simultaneously enhancing keratinocyte migration. 21 Even though all three TGFb isoforms bind to the same receptors, their effects may be different depending on genetic milieu and environment of the target cell. 5 In vitro, TGFb1 clearly promotes keratinocyte migration by increasing the expression of different integrins, which, in turn, promotes the adhesion and migration of keratinocytes.…”
Section: Tgfb Pathway In Acute Wound Healing and Epithelializationmentioning
confidence: 99%
“…1 It has been suggested that TGFb3 supports scarless wound healing through modulation of the inflammatory response and the recruitment of fibroblasts to the wound site while simultaneously enhancing keratinocyte migration. 21 Even though all three TGFb isoforms bind to the same receptors, their effects may be different depending on genetic milieu and environment of the target cell. 5 In vitro, TGFb1 clearly promotes keratinocyte migration by increasing the expression of different integrins, which, in turn, promotes the adhesion and migration of keratinocytes.…”
Section: Tgfb Pathway In Acute Wound Healing and Epithelializationmentioning
confidence: 99%
“…Most existing IH models have used rats, but both rabbits and dogs have also been used to produce experimental IH [31,32]. The majority of the existing models has been developed to investigate IH and is based on roughly the same surgical procedure as in the present model with a paramedian skin incision and a median fascial incision [12,13,14,15,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of TGFβ3 to wounds in animals has been shown to both accelerate healing and increase tissue strength in adult models. [69][70][71] It is also important to demonstrate in a clinically relevant model that the treatment has no adverse effects on wound healing (ie, is safe, well tolerated, and does not impair normal wound healing) and that systemic exposure (bioavailability) is limited at concentrations exceeding those that will be used in humans. To this end, we have recently developed a model of 20-cm full-thickness, sutured cutaneous incisional wounds in the Gottingen Minipig.…”
Section: Therapeutic Intervention: Preclinical and Clinical Studiesmentioning
confidence: 99%